Primula jiangyouensis (Primulaceae), a new species of Primula sect. Auganthus from Sichuan, China - Jiu-lin Gu; Hua-dong Wang; Hong-qiang Lin; Xiao-qi Jiang; Tian Shuai; Zhi-kun Wu (PhytoKeys)
Primula jiangyouensis J.L.Gu & Z.K.Wu, a new species of Primulaceae from Sichuan, China, is described and illustrated. Morphological evidence supports P. jiangyouensis as a member of P. sect. Auganthus, which is characterized by shallowly to deeply lobed leaves covered with hairs, and distinctively broad and flat-bottomed calyx. The new species is characterized by its branched and stout rhizomes usually up to 40 cm, yellow corollas with a distinct fan-shaped reddish-brown blotch at the base of lobes, and short glandular hair on aboveground parts. The distribution, morphological comparison with close related species and conservation status of the new species, as well as a key to the species of Primula sect. Auganthus, are also provided.